Ethnic variation of thiopurine S-methyltransferase activity: a large, prospective population study. (March 2008) - Cooper, Sheldon C; Ford, Loretta T; Berg, Jonathan D; Lewis, Matthew JV
The use of azathioprine (and its metabolite mercaptopurine) is limited by toxicity, especially myelosuppression, which is related to activity of the enzyme thiopurine S -methyltransferase (TPMT). TPMT activity varies between individuals and is considered deficient in one in 300 cases.Aims & methods: We identified TPMT activity within an ethnically diverse population of patients attending an inner-city hospital phlebotomy service. A total of 1000 subjects were recruited and analyzed with respect to age, sex and ethnicity.Results: Samples were analyzed from 456 Caucasians, 342 South Asians and 180  Afro––Caribbeans. Six subjects had deficient TPMT activity (0.6%: four women, two men; four Caucasians, one Afro––Caribbean, one South Asian). TPMT activity (nmol 6-methylthioguanine (6-MTG)/gHb/h) ranged 0––76 (median [interquartile range]: 33 [28––39]). Enzyme activity was lower in Afro––Caribbeans (30 [25––37.5]) than Caucasians (34 [29––40]) and South Asians (33 [29––38]), which was significant after adjustment for age and sex (p  <  0.0001). Activity was lower in women (p  =  0.022), especially South Asian females (n  =  194; 32 [28––36]), compared with (35 [30––40]) in men (n  =  148; p  =  0.002).Conclusions: A higher prevalence of TPMT deficiency was recorded than in previous studies. Afro––Caribbeans have lower activity than Caucasians and South Asians. TPMT enzyme activity was lower among females, especially in South Asians.